(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2022)
Most of the activities including lecturer recruiting, advertising, pupil admittance, scholar registration, educational procedures, and alumni system, most higher education institutions now use integrated information systems. The higher education information system produces a lot of transactional information, and the quantity of data is growing every day, nonetheless the best way to utilize it is yet unknown. Each piece of data saved on a data storage medium is used for a certain purpose. A higher education institution, on the other hand, requires a comprehensive understanding of all data. In light of these circumstances, an analytical tool is required to excerpt statistics and uncover useful knowledge from large amounts of data. Such procedures necessitate a longer processing time and a more complicated procedure. The goal of this study was to create a data warehouse model and dashboard for an analytical tool, as well as to apply data mining techniques to higher education institutions. The study approach started with the creation of knowledge requirements, followed by the creation of an evolutional archetype to a data warehouse, the application of data mining methods, and the creation of a console for an investigative utilities. The end consequence was basically a prototype of data mining, data warehouse, and systematic utility for higher education institutions that would help them enhance their analytical and decision-making processes and therefore improve their performance.